Determination of moisture content of maize kernel (Zea mays L.)by reflectance measurement at wavelengths 300nm to 800nm using optical technique - Norimi, Amizadillah; Abbas, Zulkifly; Jusoh, A.; Ismail, M. A.
This paper presents a method to determine moisture content of single maize kernel based on optical reflectance measurement at wavelengths from 300nm to 800 nm. The method provides a simple, fast, non-destructive and accurate technique to establish the relationship between re°ectance and moisture content. The actual amount of moisture content was determined by standard oven drying method. The optical measurement setup consists of a UV-VIS-NIR light source, an integrated set of seven 440 ¹m diameter fibers with six illumination fibers encircling one detection fiber, a spectrometer, and a sample holder ensuring that the direction of the incident beam was normal to the sample surface. The results suggest that the percentage of reflectance decreases with moisture content. Calibration equations were established at wavelengths 380 nm, 450nm and 590nm corresponding to UV-VIS boundary, carotenoid pigment absorption and yellow colour wavelengths. The lowest mean relative error of the optical fiber technique to determine moisture content based on reflectance measurements was 0.037 at 590 nm.